Evaluasi Sistem Pengendalian Intern Penjualan terhadap Peningkatan Efektivitas Penjualan Kamar: Studi Kasus pada Hotel Horison Bekasi - Triandi, Triandi; Siregar, Jahja Diapari (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2007)
This research has purpose to know the realization and the role of selling internal control system at a firm and to find out if it has significant correlation with selling effectiveness. The result of this research shows that there is strong influence of selling internal control system towards selling effectiveness. If internal control system of selling is better, selling effectiveness is better as well. Besides, internal control of selling has significant role to achieve firms goal. Keywords: Customer satisfaction; Service.